Explosive Chinese Giants: From Accounting Opacity to Threats for The Global Stock Market. The Case of Chinese Tech Companies - Ihor HURNYAK; Arkadiusz NIEDZWIECKI; Marek PRONIEWSKI (Communications of International Proceedings, 2022)
The differences in accounting standards, which are reflected in the change of the approach to valuation and revaluation of assets, essential differentiation in the regulation of audit procedures, etc., are increasingly causing the distrust of specific markets at the expert’s level. This is especially felt in the current pandemic period. It should be emphasized that not too transparent Chinese companies are perhaps the most dispersed in almost all dynamic markets in the world. Is there a danger like the crisis at the beginning of the millennium that insufficiently transparent Chinese firms may become the new Enron or WorldCom?  Among the factors ahead, we highlight in this market the strong mobilizing and supporting role of the state. On the other hand, we see some level of the institutional isolation and unpredictability of the Chinese market in terms of the application of such techniques as, for example, Fama – French model. It is not only problem that we cannot analyze the influence of individual factors, much more than that we must recognize that the model in this case is not applicable. We found confirmation for this conclusion among leading tech companies and market indices. A wide range of python packages and different approaches to portfolio optimization were used in this study.
Keywords: accounting transparency; market intelligence; stock market; Fama – French model; technology